Forbidden Love In Nizami Ganzavi‘S Layla Majnun And William Shakespeare‘S Romeo Juliet–A Comparative Literature - Sulistiani B, Martha Pardede (Pusdikra Publishing, 2022)
This thesis is entitled ?Forbidden Love in Nizami Ganzavi‘s Layla Majnun and William Shakespeare‘s Romeo Juliet-A Comparative Literature?. This thesis concern with study of comparative literature from two literary works with different nations, different culture, and different background but with similar motifs, which is Forbidden Love. This study is aiming to find out and discuss about Forbidden Love in the social context in Nizami Ganzavi‘s Layla Majnun and William Shakespeare‘s Romeo Juliet, to find out how each of the character in the two literary works dealing with Forbidden Love. The researcher take two questions that could support the statement which are: How are the nature of forbidden love in Layla and Majnun and Romeo and Juliet in the social context? And what are the similarities and differences in the two literary? In order to answer the questions, the researcher uses descriptive and qualitative research. The researcher using library research as the research method that makes the main data are novel and play which are the novel Nizami Ganjavi‘s Layla Majnun and the play William Shakespeare‘s Romeo Juliet. From this analysis the researcher expects to gathered the data with two conclusion can be clarified the problem of study in this research. The first is the researcher discovered the nature of forbidden love in the two literary works and the second is similarities and differences in the two literary works.